Bullying Prevention Approach in the Klang Valley Education Sector: Issues & Challenges - Halim Remly, Abdul; Abdul Halim, Amran; Sanusi Azmi, Ahmad; Anas, Norazmi; Muhamad Ramlan, Anaztasia Natasha (International Journal of Academic Research in Progressive Education and Development, 2023)
Bullying is a form of violence that is widespread within the education sector worldwide and has been deemed by the World Health Organization (WHO) as a global health issue affecting adolescents and children. As a result of serious injuries and even fatalities, bullying incidents in Malaysia's educational sector have gained considerable attention. Thus, the objective of this study is to analyze the preventive approaches to bullying employed in schools throughout the Klang Valley, as well as the challenges encountered in attempts to combat the crime of bullying in each institution. The study design is qualitative in nature, with case studies based on semi-structured interviews with teachers and school administrators within the Klang Valley. Six teachers/school administrators from five Klang Valley schools were chosen via purposive sampling specifically SMK Sungai Besi, SMK Taman Selayang, SK Bandar Tasik Selatan, SK Bandar Baru Salak Tinggi, and SK Rinching Hilir. Thematic analysis and ATLAS ti23 software were utilized to assess the interview findings. As per the study findings, it became apparent that the executed approaches and activities have notably contributed to a decrease in bullying cases in the study locations. The organized activities include: (i) Motivational talks, (ii) Congregational prayers and Quranic recitations, (iii) Sports and co-curricular activities, and (iv) Continuous counseling sessions. Nonetheless, schools confront a number of difficulties in implementing these ventures, including effects from gadgets, parental concerns, attendance, and external influences.